Classifying chronic pain using ICD-11 and questionnaires—reported characteristics in Japanese patients with chronic pain - Igari, Hiroki; Aono, Shuichi; Bu-Omer, Hani M.; Kishimoto, Chie; Nakae, Aya; Ushida, Takahiro (Frontiers in Pain Research, 2024)
IntroductionThe new ICD-11 code for chronic pain indicates a direction to divide chronic pain into two categories: chronic secondary pain, which has a clear underlying disease, and chronic primary pain, which is associated with significant emotional distress or functional disability and cannot be explained by another chronic condition. Until now, epidemiological studies have been hampered by the lack of a clear classification, but we believe that this new code system will provide a new perspective on the diagnosis and treatment of chronic pain, and we have begun work on this code system.MethodsWe studied 2,360 patients at Aichi Medical University, the largest pain center in Japan, and asked them to answer questionnaires on pain severity (NRS), pain-related functional impairment (PDAS, Locomo25), quality of life (EQ-5D), and psychological state and pain cognition (HADS, PCS, PSEQ, AIS) while their attending physicians were giving diagnoses according to ICD-11 and the results of the study were used to determine the coding of pain severity.Results and discussionThe ratio of primary to chronic secondary pain was almost 50%, and the group of patients with MG30.01 classification, which included fibromyalgia, had the highest severity among chronic primary pain. The MG30.01 classification of patients was also found to experience more severe pain compared to other classifications of chronic primary pain patients. The classification of patients with a major psychiatric component was not always clear, and some patients in the secondary category also had a clear psychiatric component, suggesting the need to develop complementary tools to support pain diagnosis.